The minimum data set needed for hospitals’ website to attract medical tourism - Zakieh Piri; , Mohammad hiwa Abdekhoda; Mohammadreza Alibyek; Ershad Sarbi Roghieh (Payesh, 2016)
Objective (s): Hospitals’ website has considerable potential to attract medical tourism.  Therefore, these websites should be designed based on particular features. This study was conducted to determine the minimum data set needed for hospitals’ website to attract medical tourism. Methods: This was a qualitative study. The population of this study was physicians and health information management experts. Snowball sampling was used as sampling methods. An electronic form was used to collect data. Data was analyzed by content analysis, descriptive methods and represented. Results: In all 30 physicians and experts participated in the study. The findings showed that experts indicated two main dimensions (structure and content) with 18 categories as minimum data set. In addition the analyses showed that hospitals should have website with unique URL with special attention to providing information on patient admission, information regarding services, waiting lists, and duration of convalesces. Conclusion: Hospitals that wish to contribute to medical tourism; should redesign their websites based on minimum data sets presented in this study. Structural and contextual dimensions represented in this study also should be considered, if we want to be successful in medical tourisms.